Evaluation of a crosswalk between the European Quality of Life Five Dimension Five Level and the Menopause-Specific Quality of Life questionnaire. (2nd November 2018) - Coon, C.; Bushmakin, A.; Tatlock, S.; Williamson, N.; Moffatt, M.; Arbuckle, R.; Abraham, L.
Abstract: Objectives: Postmenopausal (PM) women taking therapies using estrogens plus progestogens (EPTs) can experience side effects (breast pain, vaginal spotting/bleeding). Sensitivity of the European Quality of Life Five Dimension Five Level (EQ-5D-5L) in measuring quality of life of PM women experiencing side effects of EPTs is unknown. A crosswalk between the Menopause-Specific Quality of Life (MENQOL) questionnaire and the EQ-5D-5L was assessed. Methods: The measures were administered to 352 PM women (side effects = 202; control = 75; untreated = 75) in a non-interventional study. MENQOL total scores, treated as continuous and categorical predictors, were mapped onto EQ-5D-5L utilities using regression. Ordinary least-squares regression using averaged scores over time, goodness of fit, and estimated coefficients was also assessed. Results: Mean age was 53.7 years. The first model (MENQOL as a continuous variable) showed a moderate correlation (−0.589) and statistically significant relationship with the EQ-5D-5L ( p < 0.001), with an equation of EQ-5D-5L = 0.992 − 0.042 × MENQOL. The EQ-5D-5L mean scores were comparable (side effects = 0.854; control = 0.927; untreated = 0.836) to MENQOL mean scores estimated in the first model (side effects = 0.865 [standard deviation 0.07]; control = 0.909; untreated = 0.833). Linearity assumptions were supported with MENQOL scores as a categorical predictor. Goodness of fit was moderate ( R 2 = 0.347; root mean squared error = 0.093). Conclusion: The crosswalk supports conversion of MENQOL scores to EQ-5D-5L-derived health utilities for group-level analyses in PM women.